Pelatihan Menulis Karya Ilmiah sebagai Kegiatan Ekstrakurikuler di MTs N 5 Kota Padang - Afrini Rahmi; Asri Wahyuni Sari (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This service is carried out at MTsN 5 Padang. This service is an alternative form of learning during the pandemic. This service activity aims to help teachers and students, especially in extracurricular writing activities, to become active again. This service activity provides guidance to students both online and offline. This activity is expected to be able to hone students' writing skills in the midst of a pandemic situation that limits students' active participation, especially in extracurricular writing activities. In this activity, service is carried out using several approaches and learning models that are expected to be able to explore students' writing abilities.